Solid-state colloidal CuInS2 quantum dot solar cells enabled by bulk heterojunctions. Issue 37 (12th September 2016) - So, D.; Pradhan, S.; Konstantatos, G.
Abstract : Non-toxic colloidal quantum dot photovoltaics (CQD PV) are fabricated from CuInS2 nanocrystals, expanding the material systems used in CQD PV. Through control of device morphology, moving from a bilayer to a bulk heterojunction, the recombination from traps near the valence band is reduced. Abstract : Colloidal copper indium sulfide (CIS) nanocrystals (NCs) are Pb- and Cd-free alternatives for use as absorbers in quantum dot solar cells. In a heterojunction with TiO2, non-annealed ligand-exchanged CIS NCs form solar cells yielding a meager power conversion efficiency (PCE) of 0.15%, with photocurrents plummeting far below predicted values from absorption. Decreasing the amount of zinc during post-treatment leads to improved mobility but marginal improvement in device performance (PCE = 0.30%). By incorporating CIS into a porous TiO2 network, we saw an overall drastic improvement in device performance, reaching a PCE of 1.16%, mainly from an increase in short circuit current density ( J sc ) and fill factor (FF) and a 10-fold increase in internal quantum efficiency (IQE). We have determined that by moving from a bilayer to a bulk heterojunction architecture, we have reduced the trap-assisted recombination as seen in changes in the ideality factor, the intensity dependence of the photocurrent and transient photocurrent (TPC) and photovoltage (TPV) characteristics.